A novel allele, HLA‐A*03:01:09, identified by sequence‐based typing in a Chinese individual. Issue 6 (6th May 2013) - Liu, N.; Zhixin, Z.; Shan, X.; Wang, L.; Cui, S.
<x xml:space="preserve">Abstract</x> We describe the identification of a novel allele HLA‐A*03:01:09 in a Chinese individual.